2019
DOI: 10.1002/lary.27921
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with opioid use after endoscopic sinus surgery

Abstract: Objectives/Hypothesis Responsible prescribing of postoperative pain medications is necessary in combatting the current opioid epidemic in the United States. The goal of this study was to determine which clinical factors affect opioid usage following functional endoscopic sinus surgery (FESS). Study Design Retrospective medical records study. Methods This is a single‐institution retrospective study of subjects undergoing FESS by the senior author between September 2016 and December 2017. Opioid usage was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 19 publications
5
35
2
Order By: Relevance
“…Similar to other recent studies, our patients who underwent ESS had increased opioid consumption when a concurrent septoplasty and/or turbinoplasty was performed, and, comparable to work by Riley et al and Raikundalia et al, the extent of ESS (full vs limited) did not significantly influence pain control or opioid use . Although there are mixed results on the influence of age on opioid usage, our results are similar to others showing that younger patients require slightly more . However, as in our study with a very mild negative correlation with increasing age and other studies showing no correlation between age and opioid use, the clinical significance of this is not likely drastic .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to other recent studies, our patients who underwent ESS had increased opioid consumption when a concurrent septoplasty and/or turbinoplasty was performed, and, comparable to work by Riley et al and Raikundalia et al, the extent of ESS (full vs limited) did not significantly influence pain control or opioid use . Although there are mixed results on the influence of age on opioid usage, our results are similar to others showing that younger patients require slightly more . However, as in our study with a very mild negative correlation with increasing age and other studies showing no correlation between age and opioid use, the clinical significance of this is not likely drastic .…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, there is much to gain by looking at the similarities and differences in those studies. Similar to other recent studies, our patients who underwent ESS had increased opioid consumption when a concurrent septoplasty and/or turbinoplasty was performed, and, comparable to work by Riley et al and Raikundalia et al, the extent of ESS (full vs limited) did not significantly influence pain control or opioid use . Although there are mixed results on the influence of age on opioid usage, our results are similar to others showing that younger patients require slightly more .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other surgical factors, including revision status and concomitant septoplasty, turbinoplasty, or dacryocystorhinostomy, did not significantly affect opioid requirements. These results contrast with those of Raikundalia et al, which found that patients undergoing septoplasty had higher opioid requirements in the first 1 to 2 weeks following ESS . However, it is possible that the pain and analgesic requirements from septoplasty occur after the first 24 hours following ESS, which would have limited our ability to find this association.…”
Section: Discussioncontrasting
confidence: 84%
“…Although nonopioid medications are gaining increasing support in the literature, opioids are still commonly utilized to better control pain, accelerate patient recovery, and hasten return to normal activities . Recent studies by Jafari et al and Raikundalia et al determined that opioid use following ESS may be affected by surgical and nonsurgical factors, and that these may be used to tailor opioid prescriptions based on predicted levels of postoperative discomfort …”
Section: Introductionmentioning
confidence: 99%